RESPON PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium cepa L.) VARIETAS BIMA BREBES AKIBAT PEMBERIAN PUPUK ORGANIK TEKNOLOGI NANO - Dian Murti; Yudi Yusdian; Agus Rohimat (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2026)
The purpose of this study was to determine the concentration of nanotechnology organic fertilizer on the growth and yield of shallots of the Bima Brebes variety and to determine the concentration of nanotechnology organic fertilizer that best affects the growth and yield of shallots of the Bima Brebes variety. The experiment was conducted at the KO Diklat complex, Bumiwangi Village, Ciparay District, Bandung Regency, West Java, at an altitude of 701 meters above sea level with an average rainfall of 2,430.7 mm/year, including the C3 Rainfall type. According to Oldeman, this research was conducted from March 2025 to July 2025. The research method used was an experimental method with a Randomized Block Design (RBD) consisting of 6 treatments and 4 replications. The treatments consisted of: A 0 ml/l water, B 1 ml/l water, C 2 ml/l water, D 3 ml/l water E 4 ml/l water, and F 5 ml/l water. The results showed that a concentration of 5 ml/l nanotechnology organic fertilizer had the best effect on plant height, the number of wet bulbs per clump, and bulb weight per plot.